Continuous auditing as a tool of fiscal control: conceptual basis for application in FUNDACITE-Lara. (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
This work aims to analyze the theoretical basis for the implementation of continuous auditing as a tool of fiscal control in FUNDACITE-LARA, through intentions: (1) Focus on concepts of continuous auditing for purposes of categorization; (2) Contextualizing continuous auditing in the field of the Venezuelan fiscal control; (3) Propose the conceptual bases for the implementation of continuous auditing in Fundacite Lara. The research was part of the holistic paradigm, using as methodological tools, Model Glater, Berelson content analysis and field study, for which an observation guide and a questionnaire of 32 items, Likert scale was used. The results led to the identification of the basis for building the capacity for continuous audit of the Foundation, according to: (a) assess the effect of continuous auditing process in traditional audit; (b) establish a working methodology in accordance with the resources and capabilities of the organization and its internal auditors; (c) include specific, useful organizational aspects in the implementation of continuous auditing. Building these capabilities together with the information collected, allowed to present the conceptual basis for the implementation of continuous auditing in Fundacite-Lara, in the budgetary area.
Keywords: continuous audit; fiscal control; virtual integration